EMPOWERING PREGNANT MOTHERS TO INCREASE SELF CARE AS AN EFFORT TO PREVENT PREECLAMSIA - Faridah Umamah; R. Khairiyatul Afiyah; Fritria Dwi Anggraini; Difran Nobel Bistara; Dwinanda Djunaedi (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
Maternal Mortality Rate (MMR) is one indicator to see the success of maternal health efforts. One of the causes of AKI is preeclampsia which is the main cause of maternal and perinatal morbidity and mortality worldwide, including in Indonesia. According to the World Health Organization (WHO), one of the causes of maternal and fetal morbidity and mortality is severe preeclampsia, the incidence ranges from 0.15%-38.4%. In developed countries the incidence of severe pre-eclampsia ranges from 6-7% and eclampsia 0.1-0.7%. The incidence of pre-eclampsia in Indonesia ranges from 3-10% of all pregnancies. The maternal mortality rate in Indonesia is mostly caused by bleeding as many as 1,330 cases, hypertension in pregnancy as many as 1,110 cases, and circulatory system disorders as many as 230 cases. Therefore, it is necessary for nurses to play a role in overcoming preeclampsia, one of which is being an educator to help pregnant women reduce the risk factors for preeclampsia. The purpose of this activity is to increase the knowledge and skills of pregnant women in carrying out care during pregnancy so that they can prevent the occurrence of preeclampsia during pregnancy. The method used in this community service activity is to conduct health education about efforts to prevent preeclampsia during pregnancy at BKIA Islamic Hospital Surabaya. This activity was carried out for three months. Knowledge and skills of pregnant women in performing self-care to prevent preeclampsia were evaluated by questionnaire. The results of community service show that pregnant women have better knowledge of self-care to prevent preeclampsia.